Pengembangan Knowledge Management System (KMS) Layanan E-Government Menggunakan Metode KMSLC - Radutfa , Radutfa Samuel Jasintan Sihotang; Indah, Dwi Rosa Indah (AI Society & STMIK Indonesia, 2023)
E-government services have a role in application development, IT governance and E-government development. Employees at the Jambi Province Communication and Informatics Office (DISKOMINFO), especially in the field of E-government services, have a lot of experience and knowledge. However, it is difficult to share with other employees. Due to frequent transfers and the absence of a forum for sharing knowledge, the existing knowledge is not optimally managed. So an E-Government Service KMS is needed for DISKOMINFO in the field of E-government services. The method used is KMSLC and to capture knowledge data using On site observation in the form of interviews and observations. E-government service KMS is implemented and tested using SUS with the results of acceptable indicators and adjective ratings good